(untitled) (World Bulletin of Public Health, 2023)
Chronic obstructive pulmonary disease is one of the most common pathologies of the respiratory system and is often the cause of disability and mortality in this category of patients. Poor prognosis is often due to late diagnosis of COPD. In the last decade, certain successes have been achieved in the study of the pathogenesis, clinical picture, in the early diagnosis and treatment of COPD. Time-tested methods of diagnosing COPD continue to be used and modern diagnostic and monitoring methods (clinical questionnaires, tests, functional tests, EchoCG, multispiral computed tomography of the lungs, etc.)